2022
DOI: 10.1007/s00253-022-11981-4
|View full text |Cite
|
Sign up to set email alerts
|

HRP-conjugated-nanobody-based cELISA for rapid and sensitive clinical detection of ASFV antibodies

Abstract: African swine fever (ASF), which is caused by the ASF virus (ASFV), is a highly contagious hemorrhagic disease that causes high mortality to domestic porcine and wild boars and brings huge economic losses to world swine industry. Due to the lack of an effective vaccine, the control of ASF must depend on early, efficient, and cost-effective detection and strict control and elimination strategies. Traditional serological testing methods are generally associated with high testing costs, complex operations, and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…These provide a strong guarantee for establishing rapid and timely detection of ASFV. In addition, some studies have also reported that ASFV proteins such as p54, p30 and p72 were used for ASFV serum antibody detection [ 13 , 36 , 37 ]. The difference of sensitivity and specificity between using K205R protein as antigen and other antigens are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…These provide a strong guarantee for establishing rapid and timely detection of ASFV. In addition, some studies have also reported that ASFV proteins such as p54, p30 and p72 were used for ASFV serum antibody detection [ 13 , 36 , 37 ]. The difference of sensitivity and specificity between using K205R protein as antigen and other antigens are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to their intrinsic and unique properties, nanobodies have been widely used in the detection of specific causative agents in laboratory tests ( Salvador et al, 2019 ). More recently, several nanobodies against the p54 and K205R protein of ASFV have been isolated from the camelid immune library, they were subsequently applied in the development of nanobody-based cELISA for detection of ASFV antibodies ( Zhang et al, 2022 ; Zhao et al, 2022 ). In the present study, the nanobodies specific for native p72 protein were selected by a sandwich ELISA, and the Nb25 can specifically recognize the virus particles captured by polyclonal antibody against ASFV.…”
Section: Discussionmentioning
confidence: 99%
“…It can also illustrate epidemiological features of outbreaks such as the incubation period of the viral infection and the infections caused by the low pathogenic strains of ASFV [ 11 ]. The routine diagnostic method for ASF approved by the World Organization of Animal Health (WOAH) is the ELISA after preliminary screening, followed by Western blotting [ 12 , 13 ]. Either in endemic or ASF-free countries, the ELISA is commonly used to diagnose viral diseases and to assess serosurveys.…”
Section: Introductionmentioning
confidence: 99%
“…It will make it easier to clarify viral pathogenesis and the immune response of the host. Furthermore, in the serological diagnosis of viral diseases, mAbs are the most widely used antibodies [ 13 ]. In this study, we generated four monoclonal antibodies targeting p30, and mapped the epitope of one mAb which showed good ability to distinguish the positive and negative serum of ASF.…”
Section: Introductionmentioning
confidence: 99%